Organization of Post-Stroke Rehabilitation Services: Changes between 2013 and 2018 in Services Provided by Health System in Mongolia - Shirmen, Batchimeg; Oidov, Batgerel; Tsegmid, Narantsetseg; Bayartsogt, Batzorig; Erkhembayar, Ryenchindorj; Guntev, Tsagaankhuu; Avirmed, Baljinnyam (Central Asian Journal of Medical Sciences, 2019)
Objectives: Stroke related disabilities significantly decrease patients’ quality of life and post-stroke rehabilitation service is essential. Therefore, we studied post-stroke rehabilitation services and facilities provided in Mongolia between 2013 and 2018. Methods: A longitudinal study was performed in a total of 47 Mongolian hospitals that provide stroke rehabilitation services. A questionnaire regarding the organizational structure of rehabilitation units, equipment used, human resources, and adherence to recommended guidelines was developed and administered to specialists in these hospitals. Results: We recruited 47 (89%) out of 50 and 47 (94%) out of 53 hospitals delivering stroke rehabilitation service in 2013 and 2018 respectively. 25-34% of these hospitals provided post-stroke rehabilitation, with the majority being incapable of providing multidisciplinary team rehabilitation. The number of physiatrists and physical therapists increased significantly from 2013 to 2018 (p<.001) although the number of physical (p<.002) and occupational therapists (p<.001) was significantly lower in the rural areas. Utilization of Functional independence measures, namely, the Barthel index and modified Rankin scales were increased in 2018 compared to 2013. Conclusion: The majority of post-stroke rehabilitation services are not improved since 2013. Consistent national programs and policies are required to provide adherence to post-stroke rehabilitation guideline recommendations and implementation in clinical practice.